First ground-based charge-coupled device proper motions for fornax: II. final results - Mendez, Rene A.; Costa, Edgardo; Gallart, Carme; Pedreros, Mario H.; Moyano, Maximiliano; Altmann, Martin (The astronomical journal, 2011)
We present the first entirely ground-based astrometric determination of the proper motion for the Fornax Local Group dwarf spheroidal satellite galaxy of the Milky Way (MW), using charge-coupled device data acquired with the ESO 3.5 m New Technology Telescope at La Silla Observatory in Chile. Our unweighted mean from five quasar fields in the background of Fornax, used as fiducial reference points, leads to μαcos δ = 0.62 ± 0.16 mas yr−1 and μδ = −0.53 ± 0.15 mas yr−1. A detailed comparison with all previous measurements of this quantity seems to imply that there is still no convincing convergence to a single value, perhaps indicating the existence of unaccounted systematic effects in (some of) these measurements. From all available proper-motion and radial velocity measurements for Fornax, we compute Fornax's orbital parameters and their uncertainty using a realistic Galactic potential and a Monte Carlo simulation. Properties of the derived orbits are then compared to main star formation episodes in the history of Fornax. All published proper-motion values imply that Fornax has recently (200-300 Myr ago) approached perigalacticon at a distance of ∼150 kpc. However, the derived period exhibits a large scatter, as does the apogalacticon. Our orbit, being the most energetic, implies a very large apogalactic distance of ∼950 kpc. If this were the case, then Fornax would be a representative of a hypervelocity MW satellite in late infall.
Gesehen am 17.08.2022